Analisis profesi hakim dalam epistemologi hukum Islam - Sakirman Sakirman (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
Ethics is the foundation of a profession which becomes a common concern because of frequent misusesymptoms to the profession. The emergence of the discourse of professional code of ethics for judgesdeparted from the reality of law enforcement officials (especially judges) that ignores the values ofmorality. Although professional actors (judges) already have the code of professional conduct of judgesas moral standards, it has not been a positive impact, especially not able to change the image of societyto face justice for the better. Existing code of ethics is not providing value in favor of the realization ofthe purpose of the law, so it needs to be reviewed or revised to suit the changing situation. One way toenforce the rule of law is to enforce ethics, professionalism, and discipline. The values contained in thecode of professional conduct of judges in an ethical standpoint of Islamic law is very important to bestudied. Professional ethics of judges in principle contain moral values underlying professional personality,namely freedom, fairness and honesty. Professional ethics of judges and law is a unity that isinherently contained ethical values of Islam which is the foundation of understanding the Islamic law,so basically the code of professional conduct of judges in line with the values of the Islamic ethicalsystem. Islamic legal ethics built on four basic values which are the values of truth, justice, free will andresponsibility.